Slaughter and carcass characteristics of Malawi Zebu steers and some observations on hindquarter conformation - Butterworth, M.H.; McNitt, J.I. (1983)
Presents results of a study carried out at the Bunda College Farm of Malawi to collect data on slaughter & carcass characteristics of Malawi Zebu steers describes the correlation between linear measurements taken on the hindquarter of the live animal & hindquarter weight.